2018
DOI: 10.1097/ccm.0000000000003022
|View full text |Cite
|
Sign up to set email alerts
|

Is Overall Mortality the Right Composite Endpoint in Clinical Trials of Acute Respiratory Distress Syndrome?*

Abstract: Most deaths in acute respiratory distress syndrome patients are not directly related to lung damage but to extrapulmonary multisystem organ failure. It would be challenging to prove that specific lung-directed therapies have an effect on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Fourth, since participating investigators were asked to estimate duration of MV regardless of their probability for survival, it is plausible that they underestimated the true severity of the underlying disease and the likelihood for successful weaning and survival. Fifth, most patients died in the ICU, and the most common causes of death were similar to those from patients with severe acute respiratory failure [30], a scenario that was not anticipated in our trial design. Sixth, the strict inclusion/exclusion criteria for enrolling patients could have biased our results toward excluding difficult-to-wean patients ventilated for more than 5 days.…”
Section: Discussionmentioning
confidence: 84%
“…Fourth, since participating investigators were asked to estimate duration of MV regardless of their probability for survival, it is plausible that they underestimated the true severity of the underlying disease and the likelihood for successful weaning and survival. Fifth, most patients died in the ICU, and the most common causes of death were similar to those from patients with severe acute respiratory failure [30], a scenario that was not anticipated in our trial design. Sixth, the strict inclusion/exclusion criteria for enrolling patients could have biased our results toward excluding difficult-to-wean patients ventilated for more than 5 days.…”
Section: Discussionmentioning
confidence: 84%
“…However, for decades, it has been clear that refractory hypoxemia accounts for only a small fraction of deaths in ARDS [7,8]. A recent study showed the majority of deaths of ICU patients with ARDS were not directly related to lung damage [9]. Thus, it has been challenging to determine what proportion of mortality is attributable to ARDS itself (and therefore a potential target for ARDS-focused clinical trials), and what proportion is driven by the underlying ARDS risk factor, comorbidities, or a combination of the two.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric ARDS (PARDS), mortality rates are half of adult rates (36). Studies examining the epidemiology of cause of death in adults demonstrate that refractory hypoxemia is uncommon (7, 8), and that the majority of non-survivors die from multisystem organ failure (MSOF) or due to poor neurologic prognosis. This has relevance because interventions that target hypoxemia, such as inhaled nitric oxide (9), exogenous surfactant (10), and fluid-conservative therapy (11), have not improved mortality.…”
Section: Introductionmentioning
confidence: 99%